Green port oriented resilience improvement for traffic-power coupled networks. (September 2022) - Zhen, Lu; Lin, Shumin; Zhou, Chenhao
Abstract: Under the green ports initiative, port operations rely more on electric power. However, the power system is vulnerable to disruptions. Its ability to resist disruption seriously affects port resilience, which is related to the port operation's level and performance. To maintain a resilient port, its infrastructure needs to be well designed and coordinated to prevent or reduce losses from disruptions. Therefore, some policies are proposed to improve port resilience under various disruption scenarios by focusing on the traffic-electric power coupled system and optimizing the planning level and operational level decisions. A two-stage, stochastic, and nonlinear mathematical programming model is established to model systems' interaction and describe the impacts of preparedness and recovery actions with the objective of maximizing port resilience under a certain budget. The experimental results show that the improved coupled system can greatly improve the port resilience. In addition, the resilience of the port can also be improved by optimizing the investment in the power network and the equipment scheduling in the container transportation network. Some forward-looking managerial implications have been revealed. Highlights: Introduce the improved traffic-electric power coupled system to improve port resilience. Propose investment strategies and combination strategies to improve port resilience. Construct a mathematical model to model coupling effect between multiple networks and to quantify port resilience. Improved coupled system is highly recommended with high disruption resilient even when the cable cost is high.